Coenzyme Q10 and soyphosphatidylcholine in EK extender on preservation of Rhode Island Red poultry semen - Nath, Amit Kumar; Basu, Siddharhta; Datta, Uttam (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to evaluate the efficacy of EK extender alone or incorporation with CoenzymeQ10 (CoQ10) and/or soyphosphatidylcholine (SPC) in poultry semen and their effects on seminal traits during temporal storage at 4?C for different time intervals (12 h, 24 h, and 36 h). Heterospermic pooled semen samples diluted (1:4) with EK, EK + SPC, EK+ CoQ10 and EK + SPC + CoQ10 extenders separately, preserved and different spermiogram were assessed. Various seminal traits within the same extender differ significantly (p<0.05) among different groups and with different time intervals of storage. CoQ10 and SPC in the EK extender exhibited favorable synergistic effect on sperm quality and were able to protect the male gametes against cold-stress up to 36h at 4?C. In this study, we concluded that incorporation of SPC and CoQ10 together in EK extender possess novel potentiality to maintain seminal quality during liquid storage of poultry semen at 4?C and for their safe transportation and further use for Artificial Reproductive technologies (ARTs). http://dx.doi.org/10.5455/javar.2015.b62